Α‐synuclein conformational antibodies fused to penetratin are effective in models of Lewy body disease. Issue 8 (16th June 2016) - Spencer, Brian; Williams, Stephanie; Rockenstein, Edward; Valera, Elvira; Xin, Wei; Mante, Michael; Florio, Jazmin; Adame, Anthony; Masliah, Eliezer; Sierks, Michael R.
Abstract: Objective: Progressive accumulation of α ‐synuclein ( α ‐syn) has been associated with Parkinson's disease (PD) and Dementia with Lewy body (DLB). The mechanisms through which α ‐syn leads to neurodegeneration are not completely clear; however, the formation of various oligomeric species have been proposed to play a role. Antibody therapy has shown effectiveness at reducing α ‐syn accumulation in the central nervous system (CNS); however, most of these studies have been conducted utilizing antibodies that recognize both monomeric and higher molecular weight α ‐syn. In this context, the main objective of this study was to investigate the efficacy of immunotherapy with single‐chain antibodies (scFVs) against specific conformational forms of α ‐syn fused to a novel brain penetrating sequence. Method: We screened various scFVs against α ‐syn expressed from lentiviral vectors by intracerebral injections in an α ‐syn tg model. The most effective scFVs were fused to the cell‐penetrating peptide penetratin to enhance transport across the blood–brain barrier, and lentiviral vectors were constructed and tested for efficacy following systemic delivery intraperitoneal into α ‐syn tg mice. Result: Two scFVs (D5 and 10H) selectively targeted different α ‐syn oligomers and reduced the accumulation of α ‐syn and ameliorated functional deficits when delivered late in disease development; however, only one of the antibodies (D5) was also effective when delivered early in disease development. These scFVs were also utilized in an enzyme‐linked immunosorbent assay (ELISA) assay to monitor the effects of immunotherapy on α ‐syn oligomers in brain and plasma. Interpretation: The design and targeting of antibodies for specific species of α ‐syn oligomers is crucial for therapeutic immunotherapy and might be of relevance for the treatment of Lewy body disease.